2014
DOI: 10.1002/chem.201403370
|View full text |Cite
|
Sign up to set email alerts
|

On the Control of Magnetic Anisotropy through an External Electric Field

Abstract: The effect of an external electric field on the magnetic anisotropy of a single-molecule magnet has been investigated, for the first time, with the help of DFT. The application of an electric field can alter the magnetic anisotropy from "easy-plane" to "easy-axis" type. Excitation analysis performed through time-dependent DFT predicts that the external electric field facilitates metal to π-acceptor ligand charge transfer, leading to uniaxial magnetic anisotropy and concomitant spin Hall effect in a single mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Thus, for understanding the effect of altering the ligand, a deeper insight from DFT is necessary. DFT calculations on all the geometries of complexes 1 , 2 , and 3 are performed with the respective Cl, Br, and NCS ligands replaced by point charges of magnitude −1.0 . This calculation, on one hand, shows the effect of altering geometries on the ligand substitution as is performed experimentally in a very straightforward and convincing way, while, on the other hand, it also shows the effect of individual ligands, i.e., Cl, Br, and NCS, on the value of the ZFS parameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for understanding the effect of altering the ligand, a deeper insight from DFT is necessary. DFT calculations on all the geometries of complexes 1 , 2 , and 3 are performed with the respective Cl, Br, and NCS ligands replaced by point charges of magnitude −1.0 . This calculation, on one hand, shows the effect of altering geometries on the ligand substitution as is performed experimentally in a very straightforward and convincing way, while, on the other hand, it also shows the effect of individual ligands, i.e., Cl, Br, and NCS, on the value of the ZFS parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the DFT calculations on these complexes are in better agreement with the experimental results. Previous reports have also shown that DFT can calculate ZFS parameters for Co II complexes. ,− …”
Section: Resultsmentioning
confidence: 99%
“…As this has not been observed above 100 K, a long-lived X-ray induced excited spin-state trapping akin to optical excitations that give rise to LIESST is unlikely, but X-ray absorption spectroscopy does produce a significant photocurrent. For this reason, an electrostatic- ,,, or current-induced transient switching the molecular spin state, in the vicinity of the spin crossover transition, is possible and might be associated with a change in the dielectric constant. Steric hindrance, including crystal packing, sample conductance, and flux density, would all then play a role in determining at what temperatures this transient, not necessarily even metastable, electronic transition would occur.…”
Section: Concordance Of the Electronic And Magnetic States ?mentioning
confidence: 99%
“…An external electric field (EEF) can modulate the nature and strength of intermolecular interactions, [1][2][3][4] affect the products of known chemical processes, [5][6][7][8][9] energies of the electronic states 10,11 and consequently response properties of molecules. [12][13][14][15] The EEF has been employed for molecular sensing 16,17 and recently for catalysis. [18][19][20] Carbon nanostructures, in particular graphene, 21 because of their polarizable extended p-systems are a fascinating class of materials whose properties can be influenced considerably by means of an EEF.…”
Section: Introductionmentioning
confidence: 99%